DEFINITION OF THE TERM «RHEUMATOLOGY»: DO WE NEED THIS AND HOW DO THE EULAR AND THE ACR LOOK AT THIS? - Sh. F. Erdes (Научно-практическая ревматология)
The paper discusses the article «Common language description of the term rheumatic and musculoskeletal diseases (RMDs) for use in communication with the lay public, healthcare providers and other stakeholders endorsed by the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR)» that appeared in the on-line first journal Annals of the Rheumatic Diseases in March 2018. It is shown that, on the one hand, the development of the definition is positive, but, on the other, blurs the verges of rheumatology due to the introduction of nosological entities that are absolutely unrelated to our profession.